Social media use and protection of children’s rights (Herald of Journalism, 2022)
Similar to traditional media, such as television and radio, new social media are becoming more influential and attractive every day. The goal of the present study was to expand the scope of previous reviews on child protection issues to focus on primary and secondary school students, ages when research indicates that children begin to use mobile phones and social media.The actual issue of legal regulation of the Kazakhstan Internet space raises in the article. The author examines the issues of combining the methods of legal regulation and self-regulation on the Internet. In particular, we are talking about the fact that the threat from the Internet for children is growing every day. Prospects of soft law in the international regulation of the Internet, in countries such as the United States, Great Britain and Russia are assessed from different points of view. Especially the author draws attention to such topics as cyberbullying, hate speech, pornography and encroachment on the honor and dignity of citizens. This can be considered as the main results of the researches.      The relevance of this topic is expressed in the fact that, the Internet is still not sufficiently regulated from the legal point of view. The constant increase in the number of subscribers and the growing importance of information exchange through the network attract the public's attention to the problems of regulation, the development of rules for the fair, legitimate functioning of the Internet by the state.       The author uses methods of collecting statistical data and necessary facts, their analysis, ranking, comparison, as well as infographic methods.      The main problems of legal regulation are related to the order and conditions of the use of telecommunications networks and protection of the rights and legitimate interests of various entities during the transfer of information in global computer networks. There is a need to develop an adequate national legislation with all modern requirements.      At present, the information legislation of Kazakhstan and other neighboring countries are very extensive. However, it is still far from perfect and requires working out and adoption of new acts. This is the value of this study.  Keywords: Internet, social media, legal regulation, children's rights, blocking of information, access to information, security.